Be proactive to ensure safety of campus community. Issue 1 (10th April 2019) - Hope, Joan
Abstract : Sometimes your best efforts as a police chief can't be measured — because they prevent crime and injuries, and you don't know what would have happened without them. Scott Borden, chief of police at Rio Grande Community College and the University of Rio Grande in Ohio, takes a proactive approach to keeping his campus safe.